Internet diffusion vs. The crisis of the new economy - Domenico Campisi; Carlo Tesauro (European Regional Science Association (ERSA), 2001)
The diffusion of Internet in the world, both in terms of ''users" and "information supplyiers" is continously and constantly increasing. This market growth is based on a development that follows the usual behaviour of technological innovation diffusion (S-shaped logistic curve), so it is allowed to obtain reliable forecasts about the future market trend. Nevertheless, dispite the continous growth of the "target", the E-business seems to be in a crucial situation absolutely unpredictable since few moths ago, when viceversa looked as the main driving force of the "new economy" attacking the boundaries of the "global market". The objective of this paper is to analyse the potentialities of the growing market, through the the actual and forecasted number of users, and the condition of the general offer, in terms of typology and quality of the services supplied, trying to identify a reason for this crisis.
Keywords: 330